2011
DOI: 10.1002/acr.20609
|View full text |Cite
|
Sign up to set email alerts
|

Influence of age and sex on functional outcome over time in a cohort of patients with recent‐onset inflammatory polyarthritis: Results from the Norfolk arthritis register

Abstract: Objective. It has been found that women with rheumatoid arthritis (RA) have a poorer prognosis than men. However, the impact of age at symptom onset is unclear. We investigated the relationship between these factors and functional disability in patients with recent-onset inflammatory polyarthritis (IP). Methods. A total of 3,666 patients (66% women) were registered with the Norfolk Arthritis Register between 1990 and 2008. Functional disability was assessed using the Health Assessment Questionnaire (HAQ), adju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
19
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 21 publications
4
19
2
Order By: Relevance
“…Our findings are comparable to other studies showing a lower female predominance and less seropositivity in LORA [3,6,8,11,12]. This contrasts previous evidence of elevated RF titers due to increasing age alone; however, seroconversion over time is possible and was not formally assessed in this study [14].…”
Section: Discussioncontrasting
confidence: 78%
See 2 more Smart Citations
“…Our findings are comparable to other studies showing a lower female predominance and less seropositivity in LORA [3,6,8,11,12]. This contrasts previous evidence of elevated RF titers due to increasing age alone; however, seroconversion over time is possible and was not formally assessed in this study [14].…”
Section: Discussioncontrasting
confidence: 78%
“…Greater disability has been noted in other studies of LORA [5,7,11,12]. In a study of 1809 early RA patients from Canada, which closely resembles our study population, LORA patients were found to start and end their first year of disease with higher HAQ scores, suggesting that a difference due to age persists over time [6].…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…In a population-based cohort (n=3666) of patients with inflammatory polyarthritis, women had worse HAQ scores than men 35. Similarly, in a European MS cohort I of 1992 patients, a multivariate multiple regression analysis found that female gender was significantly associated with a lower Physical SF-36 index and higher disability level 36…”
Section: Discussionmentioning
confidence: 93%
“…[7] Moreover, most LORA patients also have comorbid diseases and additional inflammatory diseases that increase the level of functional impairment, which was already not acceptable. Rheumatoid arthritis mostly coexists with osteoarthritis (OA), and both decrease the quality of life (QoL).…”
mentioning
confidence: 99%